The printing press - Meltzer, Milton, 1915-2009 (New York : Benchmark Books, 2004)
Explains the mechanics of the first printing press, invented in Germany by Gutenberg in the fifteenth century, and describes the press's revolutionary impact on the world.
Speaking, writing, and reading -- Scribes and scrolls -- Was China first? -- How Gutenberg did it -- Printing, printing, everywhere -- The print shop : a cultural center -- From apprentice to master -- An aid to science -- From Luther to Plymouth Rock -- The printing press and democracy -- Many voices -- In love with the printed word -- The power of print -- The new place of print.
Includes bibliographical references (p. 115-118) and index.
Keywords: Gutenberg, Johann, -- ca. 1394-1468.; Printing presses -- Juvenile literature; Printing presses; Printing -- History -- Juvenile literature; Printing -- History -- Origin and antecedents -- Juvenile literature; Printing -- History